Development of Media for Class IV Students in Social - Ziyad Marta Hasdiawan; Nurul Kemala Dewi; Dyah Indraswati (STKIP Taman Siswa Bima, 2023)
This research aims to produce a ritatoon media product for the social studies subject for grade IV students which has been validated and is suitable for use in elementary social studies learning, especially on material about the socio-cultural diversity of the Indonesian nation. This research is included in development research with the ADDIE research model, namely analysis, design, development, implementation, evaluation. The results of this research indicate that the ritatoon media developed in this research is categorized as very valid. In this research, the validity value obtained from the validation results of material experts was 92%, media experts were 94%, small group student questionnaire responses were 89%, and large group were 94%. Based on the research results obtained, it can be concluded that the ritatoon media is very valid or suitable for use as a social studies learning medium for class IV elementary school.